Mentoring and Coaching Programs to Improve Performance Management - Didin Sjarifudin; Zahara Tussoleha Rony (PT FORMOSA CENDEKIA GLOBAL, 2023)
This scientific article wants to continue the study in the field of human resources by using existing variables and literature sources that will be used related to strengthen the findings of existing studies. In this article used graphic techniques are used. Analysts collect the necessary data from additional sources, analyze them, and, if necessary, modify them, additional data is used to collect information for research, books, research papers, articles, university documents, and the web is used to collect supporting data. The problem, intervention and comparison population framework (PICO) for evaluation was used to define study parameters. Coaching, mentoring programs, and performance management have been implemented with articles found from various existing literature, and described in this article, thus adding to three broader variables for other researchers to come. The results of this article provide an opportunity for other researchers to develop and use these three variables to produce other research with methods, objects, and produce a model